The tree is older than you are a bilingual gathering of poems & stories from Mexico with paintings by Mexican artists - Nye, Naomi Shihab 1952- (Aladdin Paperbacks, 1998)
A large collection of poems and stories from Native-American Indians of Mexico
Includes indexes
Gedichte spanisch und englisch
Keywords: Lyrik; Spanisch; Mexiko; Mexican literature; Mexican literature / Translations into English; Mexican poetry / 20th century; Mexican poetry / 20th century / Translations into English; Spanish language materials / Bilingual; Literatura mexicana / Literatura juvenil; Poesía mexicana / Literatura juvenil; Materiales en español; Mexican poetry; Spanish language / Reading materials / Bilingual; Bilingual books / English-Spanish; 1900-1999; Nonfiction; Read aloud books; Short stories; Poetry; Translations; Anthologie